2022
DOI: 10.1021/acs.analchem.2c00870
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Silver Nanoparticles for Rapid Serology Detection of Anti-SARS-CoV-2 Immunoglobulins G

Abstract: Dipstick assays using silver nanoparticles (AgNPs) stabilized by a thin calix[4]arene-based coating were developed and used for the detection of Anti-SARS-CoV-2 IgG in clinical samples. The calixarene-based coating enabled the covalent bioconjugation of the SARS-CoV-2 Spike Protein via the classical EDC/sulfo-NHS procedure. It further conferred remarkable stability to the resulting bioconjugated AgNPs, as no degradation was observed over several months. In comparison with lateral-flow immunoassays (LFIAs) base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…21,25–27 Very recently, we have shown that calixarene-coated AgNPs could advantageously replace gold nanoparticles of the same size ( i.e. around 20 nm) in a serological dipstick assay for the detection of Anti-SARS-CoV-2 Immunoglobulin G. 22 An improvement by one order of magnitude of the limit of detection was indeed obtained compared to AuNPs due to the better optical properties of silver. However, due to a lack of contrast with the white strip, the yellow band generated at the test line by the 20 nm AgNPs was difficult to observe with the naked eye.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,25–27 Very recently, we have shown that calixarene-coated AgNPs could advantageously replace gold nanoparticles of the same size ( i.e. around 20 nm) in a serological dipstick assay for the detection of Anti-SARS-CoV-2 Immunoglobulin G. 22 An improvement by one order of magnitude of the limit of detection was indeed obtained compared to AuNPs due to the better optical properties of silver. However, due to a lack of contrast with the white strip, the yellow band generated at the test line by the 20 nm AgNPs was difficult to observe with the naked eye.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In this context, we have recently reported the synthesis of ultra-stable Ag or AuNPs 19 and their use as colorimetric reporter in biosensing applications. [20][21][22] For this, the nanoparticles were stabilized with an ultra-thin calixarene-based layer obtained from the reductive grafting of calixarene-tetradiazonium salts. 23,24 Up to four bonds per calixarene can be formed with the surface, leading to a strongly anchored organic layer that provides extreme resistance to the nanomaterial and enables its conjugation with biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Noble nanomaterials and particularly gold nanoparticles (AuNPs) have emerged as remarkable colorimetric reporters due to their plasmonic properties. AuNPs possess a localized surface plasmon resonance (LSPR) band in the visible region that is modulated by their size, shape, and dielectric environment. Citrate-capped AuNPs (AuNPs–citrate) are the most common, convenient, and cost-effective form of gold colloids, and their synthesis via the Turkevich method is well established in the literature . AuNPs have been extensively studied, and various AuNP-based colorimetric sensors have been developed. …”
Section: Introductionmentioning
confidence: 99%
“…Spherical gold nanoparticles (AuNPs) are typically employed for colorimetric assays even though spherical silver nanoparticles (AgNPs) have an extinction coefficient that is one order of magnitude higher. , Therefore, plasmonic colorimetric biosensors that use AgNPs instead of AuNPs should result in lower limits of detection (LOD) . The reason for this discrepancy in adoption is because AuNPs have a superior colloidal stability in biological fluids and under oxidative conditions. , Although AgNPs are disadvantageous for applications where stability is of utmost importance, some groups have leveraged this instability by creating sensors that measure the optical change of pristine and degraded AgNPs in response to a target analyte. …”
Section: Introductionmentioning
confidence: 99%